2017
DOI: 10.3904/kjim.2016.367
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep quality in Behcet disease with disease activity, depression, and quality of life in Korean population

Abstract: Background/AimsSleep disturbance is prime concern in patients with Behcet disease. The purpose of this study was to find out the effects of sleep quality, in Korean patients suffering from Behcet disease. We further investigated the relationship between depression, quality of life and the clinical findings of Behcet disease.MethodsThe study was performed by the cross-sectional design. Sleep quality was assessed by the Korean version of Pittsburgh sleep quality index (PSQI). Disease activity of Behcet disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
3
19
0
2
Order By: Relevance
“…Yazmalar et al investigated the frequency of depression in BD patients using the HADS, as in the current study . In a Korean study, the proportion of BD patients with depression was 46% . Although Oktayoglu et al detected no significant difference between patients with BD and healthy control subjects in respect of HADS anxiety scores, Ilhan et al showed a significant difference between BD patients and healthy control subjects in HADS anxiety and depression scores, as in the current study .…”
Section: Discussionsupporting
confidence: 51%
“…Yazmalar et al investigated the frequency of depression in BD patients using the HADS, as in the current study . In a Korean study, the proportion of BD patients with depression was 46% . Although Oktayoglu et al detected no significant difference between patients with BD and healthy control subjects in respect of HADS anxiety scores, Ilhan et al showed a significant difference between BD patients and healthy control subjects in HADS anxiety and depression scores, as in the current study .…”
Section: Discussionsupporting
confidence: 51%
“…[11] и J. Lee и соавт. [12], показавши-ми, что РТДС при ББ ассоциируются, в первую очередь, с нарушениями сна, а также с высокой активностью бо-лезни и низким качеством жизни. Данная связь ожидае-ма, так как нарушения сна являются одним из основных симптомов РТДС [38].…”
Section: Discussionunclassified
“…Примерно у 30% пациентов с ББ наблюдаются наруше-ния сна, часто как признак РТДС [11]. Соглас-но данным корейских авторов, нарушения сна, выявленные у 42% пациентов с ББ, ассо-циировались с высокой активностью болезни, депрессией и низким качеством жизни [12].…”
unclassified
“…Thus, it can be estimated that there is a strong correlation between patients' habits and lifestyle, and patients' quality of life, which is reduced or affected through the disease activity and manifestations [21,22]. With due attention to the recent updates, several studies have suggested a strong correlation between Behcet's disease and sleep quality of the individuals [23][24][25][26][27][28]. Furthermore, it has been claimed that the mental health status could be significantly altered in patients suffering from Behcet's disease; some studies have demonstrated the high frequency of depression and anxiety in these patients [25,29].…”
Section: Introductionmentioning
confidence: 99%